Phenomenologie du christianisme africain. Une rÈflexion thÈologique sur la rÈception du christianisme en Afrique postcoloniale - Mawanzi, Cesar (Studia Oecumenica, 2012)
To engage into a new dialog between Christianity and modern African culture in post-colonial Africa is nowadays to be considered beyond doubt an inevitable assignment to African theology. The current social, political and economic life of people on the black continent demands a challenge (consideration) of the christian liberation message. In the first step of the analysis this article attempts to highlight reference points (geo-political and cultural events) which have shaped African christianity in post-colonial Africa. At this juncture the focal point is steered to what the religious and cultural heritage of numerous women and men, who have associated themselves to the message of liberation proclaimed by Jesus as the intermediary, establishes. The evangelization Africas is owed to the dedication of the pioneers, the missionaries and the preachers of the Gospel. Their commitment bears testimony to the vitality of the religious beliefs and the dynamics of cultures on the African continent. The encounter with the Christian faith has shaped the African human being, and altered his life considerably; which is not supposed to insinuate that he surrenders his cultural identity. This analysis dedicates itself to the methodic thoughts of two African theologists: On the one hand the paper is about Vincent MULAGO, an advocate of the identity movement in theology, on the other hand Jean-Marc ELA takes center stage, who is considered to be the protagonist in liberation theology in Africa. This movement campaigns for justice, for a new social order and the liberation of oppressed people. It understands itself as the attorney of the poor. In the second and third sections of the article two fundamental principles of African theology are discussed: the hermeneutic of the symbol and the proclamation of the Gospel as a liberating message. In the last point the impact of Ernst Cassirer’s philosophy of symbolic forms within African symbolic thinking is illustrated, and its lasting significance emphasized. Finally, the question regarding the ambivalent relation between confrontation and denial, stigmatization and dynamism, transformation and traditionalism in the living environment and in the living of faith of African human beings is discussed. Against this background, the exclamation of the African believer turns out to be a bold experiment, to abstain from the beaten path and options in order to settle in an experience of faith entrenched in the culture.